ANALYSIS OF BOLT JIONT STIFFNESS EFFECT WITH PRY FORCE - LIU XiaoXue; GUO HanFei; ZHANG YaHui; ZHANG YouWei (Jixie qiangdu)
Bolt joint is mostly used connection type in engineer structure for its simplicity and practicability feature,but the stiffness is changed for geometry alter which makes bolt joint design become the most important and it is essential to understand the dynamic characteristics of the whole structure. The preload and distance between centreline of bolt and prying force are discussed to confirm the affecting of stiffness. The results is shown that the initial stiffness of the structure is guarantee by preload,but the impact is more limited,preload increase of 100%,the initial stiffness increased by 13%. The distance between centreline of bolt and prying force is shorter the initial stiffness is greater,the distance is increased by 30%,the stiffness is reduced 60% reduction. Double exponential fitting formula is proposed and compared with the analysis results which provide stiffness calculation method is effect for bolt joint stiffness structures.